The Effectiveness of International Mediation as an Instrument for Human Rights Protection in Resolving Cross-Border Disputes Related to Refugee Flows - Dedy Ardian Prasetyo; Basuki Basuki (Universitas Islam Sultan Agung, 2026)
The flow of refugees across borders often triggers complex disputes that intersect with state sovereignty and humanitarian responsibility. This study aims to analyze the effectiveness of international mediation as an instrument for protecting human rights (HAM) in resolving these disputes. Using empirical legal research methods, this study evaluates the role of international mediators in bridging the interests of donor countries, transit countries, and destination countries while still prioritizing the principle of non-refoulement. The results of the study indicate that international mediation has a strategic legal position as a non-judicial dispute resolution mechanism as stipulated in the United Nations Charter, and has proven effective in breaking the deadlock in communication between countries regarding refugee flows through a flexible, confidential, and voluntary approach. Mediation can serve as a diplomatic bridge that encourages technical collaboration, while integrating human rights standards, including the principle of non-refoulement as a boundary of state sovereignty, through a strategy of humanitarian incentives and a narrative of shared responsibility. In the Indonesian context, the effectiveness of mediation is strengthened by the support of national regulations and synergy between the government, the community, and international institutions such as the United Nations High Commissioner for Refugees, although it still faces obstacles such as the unequal bargaining position of refugees, weak implementation of agreements, and legal uncertainty. Therefore, mediation needs to be strengthened by increasing the capacity of mediators and mechanisms for legalizing the results of agreements in order to provide stronger legal certainty for the protection of refugees.